RADIO SEBAGAI PROSES KOMUNIKASI MASSA - Winda Kustiawan; Azmiar Nasution; Dina Puspita Sari; Jarosim Simbolon; Sari Muliyani; Wirdatul Wisfa (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2022)
One of the signs of the era of globalization and information is the progress in the field of information technology. With information technology everything becomes easy. In the past, someone who wanted to convey a message to someone who was far away used a letter in writing using POS services, but with advances in information technology, messages can reach the recipient of the message in an instant. Such as by telephone or using other media, including in this case radio services. The existence of radio as an electronic mass media certainly makes it easier for information facilities. This is where the urgency of information technology can be used for various purposes, including being used to convey messages of Islamic teachings. In addition to radio, it can also be used as a medium that can address all levels of society. Radio has a fairly wide reach, especially when using streaming technology, it can reach all over the world. So that information can also touch all the general public.